The Influence of Digital Governance on Public Service Innovation - Rijhal, Ahmad (Asian Digital Governance Problems, 2025)
Purpose: This study examines the influence of digital governance on public service innovation in Bone Bolango Regency, Gorontalo. Digital governance is increasingly adopted to enhance transparency, accountability, efficiency, and citizen participation; however, its direct contribution to innovation in local government services remains underexplored in the Indonesian context. Subjects and Methods: The study employed a quantitative survey design involving 120 respondents consisting of civil servants and community members utilizing digital public services. Data were collected through structured questionnaires using a Likert scale and analyzed using descriptive statistics and multiple linear regression analysis. Results: The findings indicate that digital governance significantly influences public service innovation. Efficiency emerged as the strongest predictor, followed by transparency and accountability, while participation did not show a significant effect. The implementation of digital systems improved service speed, accessibility, institutional responsiveness, and public trust. Citizen satisfaction toward digital public services was generally high, particularly regarding service efficiency and accessibility. Conclusions: Digital governance has successfully strengthened administrative modernization and public service innovation in Bone Bolango Regency. Strengthening participatory governance mechanisms and digital civic engagement remains necessary to support sustainable, inclusive, and citizen-centered innovation in local public administration.